2010
DOI: 10.1038/onc.2010.168
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding zinc-finger protein tristetraprolin regulates AU-rich mRNAs involved in breast cancer-related processes

Abstract: Tristetraprolin (TTP or ZFP36) is a tandem CCCH zinc finger RNA binding protein that regulates the stability of certain AU-rich mRNAs. Recent work suggests that TTP is deficient in cancer cells when compared to normal cell types. Here we found that TTP expression was lower in invasive breast cancer cells (MDA-MB-231) compared to normal breast cell lines, MCF12A and MCF-10. TTP targets were probed using a novel approach by expressing the C124R zinc finger TTP mutant that act as dominant negative and increase ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 45 publications
2
109
0
Order By: Relevance
“…45,46 Decreased TTP expression has been suggested to contribute to cancer processes and TTP regulation of important cancer-related transcripts contributes to the suppression of invasive potential of breast cancer cells. 47,48 Furthermore, competition between TTP and HuR in binding to HuR mRNA may influence HuR overexpression and in turn an increased cytoplasmic localization within several cancers. 49 AU-binding factor 1 (AUF1; formerly known as hnRNP D) is a family of four isoforms produced by alternative splicing of a single pre-mRNA (p37, p40, p42 and p45).…”
Section: ' Utr Cis-acting Regulatory Elementsmentioning
confidence: 99%
“…45,46 Decreased TTP expression has been suggested to contribute to cancer processes and TTP regulation of important cancer-related transcripts contributes to the suppression of invasive potential of breast cancer cells. 47,48 Furthermore, competition between TTP and HuR in binding to HuR mRNA may influence HuR overexpression and in turn an increased cytoplasmic localization within several cancers. 49 AU-binding factor 1 (AUF1; formerly known as hnRNP D) is a family of four isoforms produced by alternative splicing of a single pre-mRNA (p37, p40, p42 and p45).…”
Section: ' Utr Cis-acting Regulatory Elementsmentioning
confidence: 99%
“…30 Macrophage lysates were incubated with protein-G agarose beads precoated with either rabbit anti-TTP, rabbit anti-PARP-14 or normal rabbit IgG. The beads were then washed and incubated in ribonuclease-free DNase I to remove genomic DNA contamination.…”
Section: Ripmentioning
confidence: 99%
“…uPA and uPAR are highly expressed in human glioblastoma tissue samples compared with low-grade or normal brain tissue samples (Gladson et al, 1995). Moreover, TTP has been shown to regulate uPA and uPAR expression in invasive breast cancer cells (Al-Souhibani et al, 2010). In the present study, transient overexpression of TTP in U87MG glioma cells was achieved using Ad-GFP virus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Genes that contain AREs in their 3′UTR include growth factors and protooncogenes (c-fos, c-myc, and VEGF) (Bakheet et al, 2001) as well as invasion-associated genes (uPA,uPAR, (Al-Souhibani et al, 2010). Recent studies have been shown TTP controls the decay of growth factors and proto-oncogenes (Marderosian et al, 2006).…”
Section: Discussionmentioning
confidence: 99%